Comparison of grain sorghum and alfalfa for providing heavy metal remediation of sandy soil with different soil amendments and salt stress - Mbarki, Sonia; Talbi, Ons; Skalicky, Milan; Vachova, Pavla; Hejnak, Vaclav; Hnilicka, Frantisek; Al-ashkar, Ibrahim; Abdelly, Chedly; Rahman, Md Atikur; El Sabagh, Ayman; Tlustos, Pavel (Frontiers in Environmental Science, 2022)
Soil salinity is an ongoing threat to the survival of plants and overcoming the adverse effects of saline soil on crops is crucial to achieving food security. One way to promote good plant growth under salt stress is to amend the soil with municipal solid waste compost (MSWC) or farmyard manure. The goal of this paper was to test and evaluate the effect of applications of compost or manure on tolerance to saline irrigation of grain sorghum, and alfalfa, and uptake of nitrogen, phosphorus and potassium (N, P, and K), sodium and heavy metals. Results at three harvest times (H1, H2 or H3) showed contrasting effects of harvest on plant dry weight (DW) of alfalfa and grain sorghum as the different plant species reacted differently to treatments and plant growth was significantly affected. The shoot growth was decreased by saline treatment, which was associated with high Na+ content in leaves, and this growth inhibition was mitigated in the presence of MSWC fertilizer. There was a positive correlation between shoot growth and N content for alfalfa (R2 = 0.90) and sorghum (R2 = 0.72) and K content for alfalfa (R2 = 0.69) and sorghum (R2 = 0.78). The decreased growth of the plants in the presence of salt is related to low uptake of N and K at high salt concentration. The accumulation of Na+ relative to plant DW may be an indicator of salinity tolerance of alfalfa and, similarly, heavy metal accumulation in the shoots of sorghum is a marker of heavy metal tolerance. The distribution of Cu Zn, Pb and Cu in shoots and roots is dependent on the type of heavy metal present, the plant species, and the harvest time. For both plants, shoot analysis showed no toxicity as the heavy metal concentration was below the phototoxic level.